Periodic critical micro-nutrients supplementation affects reproduction performance in peri-parturient dairy buffaloes - JYANI, VIKAS; MUDGAL, VISHAL; GUPTA, MEENAKSHI; SHARMA, RAKESH KUMAR (The Indian Journal of Animal Sciences, 2021)
The study aimed to evaluate the effect of critical micronutrient (Zn, Cu, Co, Cr, Se, vitamin E, vitamin A, and niacin) supplementation at the weekly interval during the periparturient period (56 days prepartum till 56 days post-partum) on reproduction status of Murrah buffaloes. The experiment was performed on 22 healthy Murrah buffaloes after dividing them into two equal groups, representing control and treatment, respectively. A feeding schedule of both the groups was the same except that additional micronutrient supplementation was carried out once in a week in buffaloes of treatment group after proper mixing with concentrate mixture. Ultrasonography was performed once in a month for initial 90 days postpartum for assessment of cyclicity status of buffaloes. Treatment was unable to alter the cyclicity status of buffaloes for the initial 90 days but improved the numbers of large and medium-size follicles during the due course of the study. It may be concluded that weekly supplementation of critical micronutrients during the periparturient period is helpful in improving the follicular dynamics.